1984
DOI: 10.1002/jez.1402320305
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry of the hypothalamic neuropeptides and anterior pituitary cells in the Japanese quail

Abstract: The pars distalis of the avian adenohypophysis consists of well-defined cephalic and caudal lobes which are distinct in their cellular constituents. Immunocytochemical investigations on the pituitary hormones of the pars distalis of the Japanese quail reveal five types of secretory cells, adenocorticotropin (ACTH) cells, prolactin (PRL) cells, thyroid-stimulating hormone (TSH) cells, growth hormone GH (STH) cells, and FSH/LH (gonadotropic) cells. The ACTH cells, TSH cells, and PRL cells are restricted to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The anterior lobe of the avian pituitary gland consists of well-defined cephalic and caudal lobes, and the hormoneproducing cells in these lobes show unique distribution patterns; i.e., corticotropes, lactotropes and thyrotropes are mainly distributed in the cephalic lobe (Hansen et al ., 1977;Iturriza et al ., 1980;Mikami et al ., 1984;Thommes et al ., 1983), and somatotropes are found in the caudal lobe (Hansen et al, 1977;Mikami et al, 1984). On the other hand, gonadotropes are localized in both lobes (Ravona et al, 1973;Mikami et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior lobe of the avian pituitary gland consists of well-defined cephalic and caudal lobes, and the hormoneproducing cells in these lobes show unique distribution patterns; i.e., corticotropes, lactotropes and thyrotropes are mainly distributed in the cephalic lobe (Hansen et al ., 1977;Iturriza et al ., 1980;Mikami et al ., 1984;Thommes et al ., 1983), and somatotropes are found in the caudal lobe (Hansen et al, 1977;Mikami et al, 1984). On the other hand, gonadotropes are localized in both lobes (Ravona et al, 1973;Mikami et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, gonadotropes are localized in both lobes (Ravona et al, 1973;Mikami et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…VIP is secreted by neurons which are concentrated within the mediobasal hypothalamus, in a comprehensive area referred to as the infundibular nuclear complex (INF). These neurons project to the external layer of the median eminence (ME) [7, 8, 9, 10, 11]. From the ME, VIP is transported via the hypothalamic-pituitary portal blood vessels to the anterior pituitary, where it acts on VIP receptors probably located on lactotrope cells [1, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Although the pars distalis of the pituitary gland of hagfish is simply a cell mass, that of vertebrates of an order higher than the lamprey can be divided into some regions that contain the same cell populations. The avian pituitary gland consists of well-defined cephalic and caudal lobes, and it has been shown that hormone-producing cells in these lobes have unique distribution patterns; i.e., gonadotropes are localized in both lobes [Ravona et al, 1973;Mikami and Yamada, 1984;Sasaki et al, 2003], whereas cortico-Nakamura/Iwasawa/Kidokoro/Komoda/ Zheng/Maseki/Inoue/Sakai tropes, lactotropes and thyrotropes are mainly distributed in the cephalic lobe [McKeown, 1973;Ferrand et al, 1974;Hansen and Hansen, 1977;Jozsa et al, 1979;Sharp et al, 1979;Iturriza et al, 1980;Thommes et al, 1983;Mikami and Yamada, 1984;Berghman et al, 1993;Reichardt, 1993;Sasaki et al, 2003]. On the other hand, somatotropes are found only in the caudal lobe [Hansen and Hansen, 1977;Mikami and Yamada, 1984;Sasaki et al, 2003].…”
Section: Introductionmentioning
confidence: 99%